Effect of Security and Confidentiality and Readiness of Information Technology on the Use of E-Filing - Muhammad Adil; Endang Winarsih; Wahyuni (Jurnal Economic Resource, 2021)
This study aims to examine and analyze the effect of security and confidentiality and information technology readiness on the use of e-filing. This study involved 100 respondents from 35,698 registered taxpayers and was calculated using the Slovin formula. Determination of the sample using the purposive sampling technique. The data in this study were collected by distributing questionnaires to respondents. After the data is collected, then data analysis is carried out using descriptive statistical analysis methods, instrument testing (validity test and reliability test), classical assumption test (normality test, multicollinearity test, heteroscedasticity test, and linearity test), and hypothesis testing (linear regression equation test). Coefficient of determination test, and t statistic test). Based on the research results, Security and Confidentiality has a positive and significant influence on the e-filing system, which means that the higher the security and confidentiality, the higher the use of e-filing. Also, Information Technology Readiness has a positive and significant influence on the use of the e-filing system, which indicates that the higher the perception of Information technology readiness in accessing the e-filing system, the higher the use of e-filing. The inappropriate distribution of questionnaires and the number of samples that are still lacking are limitations in this study. Future researchers are expected to carry out research at the right time and increase and expand the number of samples. In addition, the use of the interview method to respondents can maximize critical answers to the research results.